Validación de un test para verificar si el alumno posee concepciones científicas sobre calor, temperatura y energía interna - Lang da Silveira, F.; Moreira, Marco Antonio (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
This study is a continuation of the task of validating a paper and pencil test to check whether the student has scientific conceptions about heat, temperature and internal energy in which we are working since 1989. The third version of this instrument is presented here. Previous versions (Silveira, Moreira and Axt, 1990,1991) were modified after an analysis of internal consistency carried out with additional data provided by 168 students of introductory physics at UFRGS. The present version is constituted by 23 items, which might be divided into three groups, each one corresponding to one of the three concepts: heat, temperature and internal energy. This division is based on a logical content analysis as well as on an empirical analysis of students’ responses.